Production of polyketides with anthelmintic activity by the fungus Talaromyces wortmannii using one strain-many compounds (OSMAC) method. (December 2016) - Liu, Wen-Cai; Yang, Fan; Zhang, Ran; Shi, Xuan; Lu, Xin-Hua; Luan, Yu-Shi; Xiu, Zhi-Long; Dong, Yue-Sheng
Graphical abstract: Highlights: OSMAC strategy could increase the kind of wortmannilactones. Three new wortmannilactones, wortmannilactones I1-I3, were isolated from medium of Talaromyces wortmannii . Their structures were assigned by IR, HRESIMS, NMR and ECD. These new wortmannilactones exhibit selective inhibitory activity against NADH-fumarate reductase. Abstract: Three new polyketides, wortmannilactones I1-I3, were purified from Talaromyces wortmannii using the One Strain Many Compounds (OSMAC) strategy. The polyketides' structures were established using IR, 1D and 2D NMR, and HRESIMS analyses and the absolute configurations were identified by comparison of experimental and calculated ECDs. These polyketides exhibit selective inhibitory activity against NADH-fumarate reductase.